2015
DOI: 10.1038/cddiscovery.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Heme-based catalytic properties of human serum albumin

Abstract: Human serum albumin (HSA): (i) controls the plasma oncotic pressure, (ii) modulates fluid distribution between the body compartments, (iii) represents the depot and carrier of endogenous and exogenous compounds, (iv) increases the apparent solubility and lifetime of hydrophobic compounds, (v) affects pharmacokinetics of many drugs, (vi) inactivates toxic compounds, (vii) induces chemical modifications of some ligands, (viii) displays antioxidant properties, and (ix) shows enzymatic properties. Under physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 92 publications
2
52
0
Order By: Relevance
“…Recently, some researchers had found that some variations in the V-shaped cavity of SAs from mammals, apes, reptiles, amphibians, and fish could be associated with the FA1 binding site for heme, bilirubin, fatty acids, and various exogenous compounds. 9 , 10 In contrast, PR has been shown to bind to Sudlow’s site II, which is located at some distance from the FA1 site (IB) and in the different subdomain (IIIA) of SA. 5 , 8 On the other hand, the pharmacokinetics and pharmacodynamics (PK/PD) analysis of PR was conducted mainly in animals, including mice, rats, dogs, and so forth, which might impose big difficulties when comparing these data with those of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers had found that some variations in the V-shaped cavity of SAs from mammals, apes, reptiles, amphibians, and fish could be associated with the FA1 binding site for heme, bilirubin, fatty acids, and various exogenous compounds. 9 , 10 In contrast, PR has been shown to bind to Sudlow’s site II, which is located at some distance from the FA1 site (IB) and in the different subdomain (IIIA) of SA. 5 , 8 On the other hand, the pharmacokinetics and pharmacodynamics (PK/PD) analysis of PR was conducted mainly in animals, including mice, rats, dogs, and so forth, which might impose big difficulties when comparing these data with those of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Each study week, two of the eight animals were randomized as described above, desensitized, and then administered either intravenous human Hp (2‐1 and 2‐2) plasma fraction concentrates (800 mg/kg total dose, in two divided 100 mg/kg bolus doses at 4 and 7 h after bacterial challenge, followed immediately by a 600‐mg/kg continuous infusion over 48 h) or administered an equivalent volume of phosphate‐buffered saline as previously described . Albumin was not used as the control solution in the second set of experiments to avoid binding heme, which is expected to increase after hemolysis . This study was stopped early due to the toxicity seen with Hp therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Hemozoin, an insoluble crystalline of free heme, is essential to survive in hematophagous organisms, such as malaria parasites. In Vertebrates, free heme is specifically scavenged by extracellular heme-binding protein hemopexin, and alpha-1-microglobulin, or, by serum albumin [64]. Besides, HOs also protect cells from heme toxicity by catabolizing heme into iron, biliverdin, and CO.…”
Section: Heme-induced Toxicitymentioning
confidence: 99%